Sulfur source-mediated transcriptional regulation of the rhlABC genes involved in biosurfactants production by Pseudomonas sp. strain AK6U - Ismail, Wael; El Nayal, Ashraf M.; Ramadan, Ahmed R.; Abotalib, Nasser (Frontiers in Microbiology, 2014)
Despite the nutritional significance of sulfur, its influence on biosurfactants production has not been sufficiently studied. We investigated the expression of key biosurfactants production genes, rhlABC, in cultures of Pseudomonas sp. AK6U grown with inorganic or organic sulfur sources. AK6U grew with either inorganic sulfate, dibenzothiophene (DBT) or DBT-sulfone as a sole sulfur source in the presence of glucose as a carbon source. The AK6U cultures produced variable amounts of biosurfactants depending on the utilized sulfur source. Biosurfactants production profile of the DBT cultures was significantly different from that of the DBT-sulfone and inorganic sulfate cultures. The last two cultures were very similar in terms of biosurfactants productivity. Biosurfactants yield in the DBT cultures (1.3 g/L) was higher than that produced by the DBT-sulfone (0.5 g/L) and the inorganic sulfate (0.44g/L) cultures. Moreover, the surface tension reduction in the DBT cultures (33 mN/m) was much stronger than that measured in the DBT-sulfone (58 mN/m) or inorganic sulfate (54 mN/m) cultures. RT-qPCR revealed variations in the expression levels of the rhlABC genes depending on the sulfur source. The DBT cultures had higher expression levels for the three genes as compared to the DBT-sulfone and inorganic sulfate cultures. There was no significant difference in the expression profiles between the DBT-sulfone and the MgSO4 cultures. The increased expression of rhlC in the DBT cultures is indicative for production of higher amounts of dirhamnolipids compared to the DBT-sulfone and inorganic sulfate cultures. The gene expression results were in good agreement with the biosurfactants production yields and surface tension measurements. The sulfur source mediates a fine-tuned mechanism of transcriptional regulation of biosurfactants production genes. Our findings can have an impact on industrial production of biosurfactants and other biotechnological processes like biodesulfurization